Educação para o consumo na organização aprendente educativa como instrumento determinante na relação sustentável entre ser humano e meio ambiente - Cavalcanti, Petrônio Santos (2016)
The consumer education as a decisive instrument in the relationship between human beings and the environment is the purpose of this production. As a research field, the State School Moyses Barbosa city of Petrolina, where they study about 950 students and 80 employees work. Field favors significantly to research on education that fosters new practices in relation to consumer habits and has decisive influence on the existence of a sustainable environment. Consuming is a human need, it is inherent in the existential process; already consumerism unleashed by called hypermodern society, precisely originated in the nineteenth century, it is predatory and harmful to the environment. With consumerism, the person becomes merchandise, products replace the subject, human subjectivity is hidden and it is evident the object. In this case, when the human being loses his identity, it is not capable of self-knowledge and not knowing the other as a person. In the alienated situation where it is not able to be autonomous, authentic, the environment is in danger, to be devalued and put the banks without proper care, that are necessary for a good experience. The truth is that human actions, if not consider the reason, consciousness, emotion, desire, the logic that are pertinent to be, can hinder the existence of a good relationship between man / woman and nature. What is notable in this work is the need for pedagogically educate the subject to consumption, since there are no conditions to inhabit the planet without the exercise of care. In this study, we recognize the role of learning organizations, which lets you experience the tacit and explicit knowledge, this and developed the information, the data, the readings and the use of technology. Thus, this study was prospective, through qualitative approach and action research foundations, understand the importance of consumer education as key tool to influence the behavior of people who need to learn to live in an ethical and sustainable way the environment. The techniques used for building data - observation and interview favored the investigation without responsibility consumption problem and the impacts they have on the environment of consumerism practices characteristic of contemporary society. The interview was policy and addressed 62 people between students and educators. Each answer was carrying substantial elements to understand the education brief reflection on the problem, which affects the lives of people and other beings, consumption without responsibility. In this sense, the final results of the research pointed to the viability of education that guides the act of consuming, to care for and preserve the environment.